(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2026)
In today’s education system, academic success is often seen as the primary determinant of a child’s future. This intense focus on competition can lead to significant psychological challenges, including anxiety, depression, loneliness, and confusion, ultimately affecting children’s overall development. To counter these negative effects, it is crucial to foster intellectual growth that respects and nurtures a child’s individuality. Rooted in ancient Indian wisdom, the Bhagavad Gītāencapsulates the essence of self-realization or “God-Realization.” It emphasizes the singular goal, acknowledging the diversity of the paths available, based on every human’s individual situation and capacity. In recent times, there has been an increasing recognition of the relevance of the teachings of the Bhagavad Gītā. The key lies not in the text itself, which connects God, soul, mind along with the true spirit of selfless action but in the way verses of Bhagavad Gītā as a part of the Indian Knowledge System help in guiding towards holistic human well-being. The paper is an attempt to study the verses of Bhagavad Gītā and underscores its importance in enhancing the quality of life and creating a sustainable future. It also aims to delve in understanding the world in a deeper context for a sustainable growth and the role Bhagavad Gītācan play as a roadmap for spiritual emancipation.